PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH BERBANTUAN MEDIA SCRAPBOOK DALAM PEMBELAJARAN IPS KELAS IV SD NEGERI KALIBENING - Avivah Oktaviana; Supriyanto Supriyanto; Asep Sukenda Egok (LP4MK STKIP PGRI Lubuklinggau, 2023)
This research aimed to determine the completeness of social studies learning outcomes for Class IV of SD Negeri Kalibening after applying the Make A Match learning model assisted by Scrapbook media. The research method used in this study is the Pre-Experimental Design with the form of the design used, namely the One-Group Pretest-Posttest Design. The population is the entire fourth grade of Kalibening Public Elementary School, and the research sample totals 14 students. Data collection techniques include interviews and tests. The data analysis technique used the normality test and the Z test. The results showed that the average student's final test score was 76.64, and the percentage of students who passed was 12 (85.71%). Based on the results of data analysis, it shows that Zcount = 5.39 and Ztable = 1.64 (Zcount > Ztable). Thus it can be concluded that the social studies learning outcomes for Grade IV SD Negeri Kalibening after the application of the Make A Match learning model assisted by Scrapbook media are significantly complete.